The Internationalization Process of the Firm : Searching for New Patterns and Explanations - .Nordström, Kjell A. (Institute of International Business. Stockholm School of Economics, 1991)
Allting ar orsakslost... Nar det intraffar att man inser detta, far man kvaljningar och allting borjar gunga... Jean-Paul Sartre.